Abjection, gender violence and andean gothic in ‘Sangre coagulada’, by Mónica Ojeda - Leonardo-Loayza, Richard (2024)
The article analyzes ‘Coagulated blood’ (2020) by Mónica Ojeda. It is intended to demonstrate that in said text a complaint is presented against the violence suffered by women, but also, the capacity of the latter to face such violence. Ojeda tells the story of a disabled teenager, who was the victim of a sexual assault and is disowned by the rest of the town due to her strange behavior and because her grandmother performs abortions. In this context, the story shows how the adolescent, who is considered abject (Kristeva), develops the capacity for agency (Sen), thanks to the affidamento (Milan Women's Bookstore) that she achieves by living with her grandmother. By virtue of the above, La Ranita, as the girl is called, learns to face the people who try to attack her and her family. To tell the story, Mónica Ojeda appeals to andean gothic, an aesthetic that uses andean magical mythical references as a substrate.